Retina the real time interactive solution for visually impaired - N. Ramya, Mrs.; Akshai, R; Baba Skandar, R; M. Balamurugan, S (International Journal of Engineering and Technology, 2018)
The main objective of the project is to provide an application that acts as an all-in-one tool for disabled people. Most activities are performed digitally, a prime example being online shopping platforms which have replaced the traditional means. In this era of modern technology, people are entirely reliant on electronic gadgets and make use of several features to run their daily lives. To enhance the usability of such features for disabled people, this application has been developed to take care of their basic needs. The dependence of the general public on mobile applications is justified but that is not the case for disabled people. This application has been designed specifically to cater to such people with disabilities. This proposal requires our â€œRetina Appâ€ and breath analyzer module only. The differentiating feature of this appli-cation is the ability to perform various functions such as booking an Uber, reserving tables at restaurants, calling ambulances and fire trucks in addition to the detection of diseases. It can detect the level of alcohol in a personâ€™s breath and when it surpasses a certain level, it displays a notification which can help the user to book a cab directly to take him/her back to his/her residence..Â Â